Additional file 5 of Steep intraplate reverse faulting adjacent to the hypocenter of the 1923 Kanto earthquake: the Mw 5.0 western Kanagawa earthquake in eastern Japan on 9 August 2024 - Yasunori Sawaki (22685773) (2025)
Additional file 5. A CSV file for the fault parameters of the extracted planes in Fig. 3 (Table S5; data set generated in this study). Starting from the left, the “index_cluster” denotes the cluster numbering (the same in Additional file 4). The “num_clusters” column is the number of events in the cluster. The next four columns are “strike”, “dip”, “length”, and “width” of the extracted planes. The “xi”, “eta”, and “n” are the strike $${\varvec{ξ}}$$ ξ , dip $${\varvec{ξ}}$$ ξ , and normal $$\widehat{{\varvec{n}}}$$ n ^ vectors of north, east, and depth components, respectively. The “variance_normal” and “variance_ratio_normal” are the PC3 eigenvalues and their contribution rates, respectively. The “planarity” column represents the fraction of PC2 to PC3 eigenvalues for each cluster. The “median_angle_diff” column denotes the median angle between the fault normal direction $${\widehat{{\varvec{n}}}}_{i}^{\text{FP}}$$ n ^ i FP and each point-cloud normal vector $${\widehat{{\varvec{n}}}}_{ij}^{\text{EV}}$$ n ^ ij EV in the cluster $${C}_{i}$$ C i (Sawaki et al. 2025b). “R0” to “R3” columns are the four corners of the extracted rectangles of north, east, and depth components, respectively. The edge connecting “R0” and “R1” represents the top of the fault plane.